Resiproritas Antar Petani dalam Tradisi Alap Ari Turun Tanam dan Panen Padi di Desa Terang Bulan Kecamatan Aek Natas - Munthe, Mona Ratu; Amal, Bakhrul Khair (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Reciprocity refers to an exchange system carried out using reciprocal relationships. This research aims to describe and analyze exchanges between farmers in the alap ari tradition. The method used in this research is qualitative with a descriptive approach. This research is in Terang Bulan Village, Aek Natas District. Data collection techniques are through observation, in-depth interviews, and documentation. The results of the research show that the exchange patterns that occur between farmers using a reciprocity system are comparable and negative. Farmers use a system of exchange of services and money, where the exchange system carried out by farmers is a tradition that has existed for a long time which means working together and helping each other in completing all the work in the farmer's rice fields, basically, this tradition is called alap ari is referred to as proportional reciprocity which is an activity that simplifies, speeds up and eases all the work of farmers. Meanwhile, negative reciprocity is the existence of a wage system, so the tradition of helping voluntarily has begun to be abandoned by farmers in the village. So, researchers are interested in seeing the reasons why farmers switch to using money or a wage system to complete all their work in the fields